Positively energizing leadership : virtuous actions and relationships that create high performance - Cameron, Kim S. (Berrett-Koehler Publishers, 2021)
"This practical guide, the first to show how leaders can achieve extraordinary results through the positive energy generated by virtuous interactions with employees, is written by one of the giants in the study of positive leadership"--